Cable Car Speed Control Using Programmable Logic Control Based on Fuzzy Logic - Santi Triwijaya; Arief Darmawan; Andri Pradipta; Dara Aulia Feriando (Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2020)
A cable car is a hanging car that runs by cable. Cable car carrier controlled by DC motor. The cable car can be a solution to accommodate the mobilization of agricultural commodities in areas that are difficult to access while still paying attention to safety and reliability. In this research, the speed of a cable car would be automatically controlled with Programmable Logic Control (PLC). PLC functions as a cable car operation controller by considering 3 parameters, namely: wind speed, maximum load weight, and distance (meters). The speed of the cable car is controlled by the PLC using fuzzy logic. Cable car speed is based on parameters of wind speed, load weight and distance. From the results obtained, the PLC has worked well in regulating the speed of the cable car and if any parameter exceeds the PLC limit, it can turn off the cable car.